ORGANIZATIONAL CULTURE AND JOB SATISFACTION AFFECT TEACHER PERFORMANCE AT KELING KUMANG SEKADAU VOCATIONAL SCHOOL - Adil Bertus; Fitria Elvi; Jonathan Giovanni (SEAN Institute, 2023)
Keling Kumang Vocational School is a vocational high school with the most students in Sekadau District. Of course, the success factor of the school is the teachers' performance and how the organizational culture is an important factor in improving teacher performance in carrying out every activity at school. Another thing that is no less important is teachers' job satisfaction as a driving force in doing work. Therefore the purpose of this research is to find out